Gender Role Conflict among Malay Adolescent Boys in Malaysia - Mansor, Noorazida Zaharah; Othman, Zahiruddin; Yasin, Mohd Azhar Mohd; Husain, Maruzairi; Yaacob, Mohd Jamil (Japan International Cultural Exchange Foundation, 2014)
Background: Modernization process brings in economic and demographic changes where traditional masculinity could be forced to transform as men face conflicting messages about appropriate role norms. Objectives: This study aimed to evaluate gender role conflict (GRC) among Malay adolescent boys and its associated socio-demographic factors using the newly validated Malay GRCS-A. Methods: A total of 282 Malay adolescent boys aged 13-17 from 6 secondary schools in Kota Bharu, Kelantan were randomly selected and evaluated using the Malay GRCS-A and DASS-21 to assess GRC and psychological wellbeing respectively. Results: GRC was significantly associated with anxiety and stress, but not with depression. Regression analysis showed GRC was positively correlated with upper secondary school (older age) and negatively correlated with separated parents and very low household income (< RM 1,000 per month). Conclusion: This study adds to the growing literature of GRC, particularly in the Malay adolescent boys. High GRC potentially worsen the already high prevalence of psychological distress among adolescents in Malaysia